Hagaras an Archetype Matriarch: A Comparative Study of Ostriker’s “The Opinion of Hagar”and Kahf’s “Hagar in the Valley” - الشايع، سهير نافع عبدالعزيز; فؤاد، جيهان فاروق; حسب النبي، ماجدة منصور محمد (جامعة عين شمس - كلية البنات للآداب والعلوم والتربية, 2016)
يسلط البحث الضوء على شخصية هاجر والتي تعتبر واحدة من الأمثلة الأكثر تناولاً كنموذج للأم في الدراسات اليهودية والإسلامية. وتفترض الباحثة ان كلا الشاعرتين أليشا اوسترايكر الشاعرة والناقدة الامريكية اليهودية الأصل ومهجه قحف الشاعرة الأمريكية ذات الأصول العربية قد حاولتا قراءة وتحليل قصة هاجر من وجهة نظر نسوية. الدراسة شملت قصيدة اوسترايكر "رأي هاجر" وقصيدة قحف". كلا الشاعرتين تناولتا القصة حسب ما لديهما من الإرث والكتب الدينية التي يمثلوهما. من خلال قصة هاجر عكست الشاعرتين قضايا وثقافات معاصرة ومنها التمييز ضد المرأة وما تواجهه المهاجرات من صعوبات. مع هذا نجد لكل شاعرة طريق وأسلوب مختلف بالتعامل مع القصة الاصلية. حيث ان تفسير قصة هاجر قد اعتمد على خلفية الشاعرة الدينية وما تملكها من مصادر وفهم خاص لنظرية المعالجة النصية. كلا القصيدتين يمكن اعتبارهما كصوت نسائي مهم في تطور تاريخ النساء الديني في الولايات المتحدة الامريكية. فالشاعرتين قد وضعتا قصة هاجر كأسطورة دينية وكمفتاح لحوار الثقافات بين اليهودية والإسلام.
This paper marks out the archetype figure of Hagar, one of the most revisited examples of motherhood in the corpus of Islamic and Jewish studies. The researcher shows that both Alicia Ostriker, Jewish-American poet and critic (born 1938), and Mohja Kahf, an Arab-American poet (born 1967), attempt feminist readings of Hagar’s story. The study tackles Hagar in Ostriker’s poem “The Opinion of Hagar” and Kahf s “Hagar in the Valley”. Both poets retell their traditional Jewish and Muslim narratives and depend heavily on scriptures and religious heritage. Through Hagar’s story, they both reflect on contemporary cultural issues; discrimination against women and the hardships faced by immigrants are two main issues that Ostriker and Kahf see in the story of Hagar. Yet each poet has a different focus and different manners based on adaptation and appropriation of the original story. The reinterpretation of Hagar’s narrative depended on the poets’ religious sources, as well as on each poet's reception of the narrative. The two poems of ‘Hagar’ are considered a recovery for the female voices that have played a significant role in the development of women’s religious history in the United States of America. With intertextuality, the two poets situate the narrative of Hagar as an archetypal and mythical figure for all women and as a key text in interfaith dialogue between Judaism and Islam.
Keywords: الأمومة -- السيدة هاجر -- قصيدة رأي هاجر -- قصيدة هاجر في الوادي -- أوسترايكر، أليشا -- قحف، مهجه